Efficacy of Freeze Dried Inactivated Equine Influenza, Equine Herpesvirus-1 and Tetanus Toxoid Vaccine - Madkour, Nashwa K.; Ebeid, Eman M.; Saleh, Nehal S.; Warda, Fatma F.; El-Helw, Hamed A.; Abd El-Bakey, Aliaa (Journal of Advanced Veterinary Research, 2023)
Vaccination has a very important role in controlling the most infectious diseases in horses especially Equine Influenza Virus (EIV), Equine Herpesvirus-1 (EHV-1) and Tetanus. The keeping quality of the locally prepared combined inactivated vaccine containing EIV, EHV-1 and Tetanus Toxoid (TT) adjuvanted with saponin and Alhydrogelwere improved through preparingthe lyophilized inactivated EIV, EHV-1 and TT vaccine then reconstituted with adjuvant (saponin) and compare between them (liquid and lyophilized). The two vaccine batches were inoculated into groups of guinea pig and horses for potency and immunogenicity measurement. The immune response in guinea pigs and horses measured by HI test for EIV and ELISA for EHV-1 and Toxoid Neutralizing antibody test (TN) for T.T which proved that antibody was detected at 2weeks post vaccination reached its peak at two-month post inoculation (2MPI) then declined gradually until 7MPI. There is no significant difference between all vaccines, as they were potent, efficient and immunogenic. Regarding to the keeping quality, the tested vaccine vials were keptat 4ºC for various interval times (1, 2, 2.5, and 3years) then inoculated into guinea piggroups. Finally, the lyophilized vaccine was proved to be stable and potent for 3years while the liquid vaccine was stable for 2years.